[MG49-LiClO4]:[TiO2-SiO2] Polymer Electrolytes: In Situ Preparation and Characterization - Oon Lee Kang; Azizan Ahmad; Nur Hasyareeda Hassan; Usman Ali Rana (International Journal of Polymer Science)
In the present research, [MG49-LiClO4]:[HNO3-THF/TiO2-SiO2] and [MG49-LiClO4]:[ClHNO2-THF/TiO2-SiO2] polymer electrolytes were first prepared through simple stepwise in situ techniques: sol-gel technique and solution-cast technique. [MG49-LiClO4]:[HNO3-THF/TiO2-SiO2] and [MG49-LiClO4]:[ClHNO2-THF/TiO2-SiO2] polymer electrolytes were then characterized through different experimental techniques. [MG49-LiClO4]:[HNO3-THF/TiO2-SiO2] and [MG49-LiClO4]:[ClHNO2-THF/TiO2-SiO2] polymer electrolytes had exhibited significant structural changes upon different salt concentrations. In the present investigation, [MG49-LiClO4]:[HNO3-THF/TiO2-SiO2] and [MG49-LiClO4]:[ClHNO2-THF/TiO2-SiO2] polymer electrolytes had attained maximum ionic conductivities (σ~10-7 S/cm at ambient temperature; 10−4 S/cm at 100°C) upon 25 wt.% salt insertion. [MG49-LiClO4]:[HNO3-THF/TiO2-SiO2] and [MG49-LiClO4]:[ClHNO2-THF/TiO2-SiO2] polymer electrolytes had exhibited distinct conduction mechanisms in similar experimental configuration. [MG49-LiClO4]:[HNO3-THF/TiO2-SiO2] and [MG49-LiClO4]:[ClHNO2-THF/TiO2-SiO2] polymer electrolytes had exhibited different stability characteristics over certain operational condition.